Liquid crystals : applications and uses - Bahadur, Birendra (World Scientific, 1992)
This book reviews comprehensively the technological, scientific, artistic and medical applications of liquid crystals. It starts with the basics of liquid crystals and covers electro-optical, thermo-optical, colour, polymeric, lyotropic, and scientific applications of liquid crystalline materials. It discusses the fabrication and operational principles of a full range of liquid crystal displays including dynamic scattering, twisted nematic, supertwisted nematic, dichroic, smectic A, ferroelectric, polymer dispersed, light valve, active matrix, etc., in detail. It also covers the emerging applications of liquid crystals such as optical computing, nonlinear optics, decorative and visual arts. The detailed chapters on classification, theory, chemical structure, physical properties and surface alignment of liquid crystals facilitate the basic understanding of the science behind LCDs and other uses of liquid crystals. The chapters on liquid crystal polymers and lyotropic liquid crystals, give deep insight into these areas. The potential uses and applications are also described in detail.